2020
DOI: 10.3390/en13071677
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of VSC–HVDC Reactive Power Control Mode on AC Power System Stability

Abstract: Voltage source converter-based high-voltage direct current (VSC-HVDC) has the advantage of fast and independent controllability on active and reactive power. This paper focuses on effects of commonly proposed reactive power control modes, constant reactive power control and AC voltage margin control. Based on the mathematical model of single machine infinity equivalent system with embedded VSC-HVDC, the influence of VSC-HVDC with different reactive power control strategies on transient stability and dynamic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Ying Wang et al in [12] focus on effects of commonly proposed control modes for a voltage source converter (VSC)-based HVDC systems. The influence of VSC-HVDC with different reactive power control strategies on transient stability and dynamic stability of the AC system is studied.…”
Section: Published Papers Highlightsmentioning
confidence: 99%
“…Ying Wang et al in [12] focus on effects of commonly proposed control modes for a voltage source converter (VSC)-based HVDC systems. The influence of VSC-HVDC with different reactive power control strategies on transient stability and dynamic stability of the AC system is studied.…”
Section: Published Papers Highlightsmentioning
confidence: 99%
“…representing loss components of voltage magnitude are obtained from ( 23) and (24), respectively but derivatives for the loss angle components equals zero as a result of dc components, hence;…”
Section: Vsc-hvdc Sensitivity Based Optimal Placement Approachmentioning
confidence: 99%
“…In a similar work, the control parameters of VSC were tuned using particle swarm optimization algorithm (PSO) for steady state and dynamic performance enhancement of VSC-HVDC system [23]. Wang et al, studied the effects of dissimilar reactive power control strategies on transient and dynamic stability of an ac system, with conclusion that oscillation control and voltage sustenance were influenced especially at the instance of grid disturbance [24]. It was concluded in [25] however, that VSC-HVDC have an impact on interdependency of power system dynamics and that further studies are required to fully understand their impact on system stability improvement and ancillary support services.…”
Section: Introductionmentioning
confidence: 99%
“…VSC-HVDC technology is a promising solution for integration of future offshore wind farms into the existing AC system and also an attractive bulk power transmission structure in the next-generation networks [1]. VSC-HVDC can contribute to voltage stability improvement during severe disturbance [2][3][4][5][6][7][8][9][10][11][12][13], while the control schemes of the VSC-HVDC play an important role in the enhancement of the voltage stability [2][3][4][5][6][7][10][11][12][13]. In recent years, there are a number of research efforts focusing on the voltage stability of multi-terminal HVDC networks [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is also found that the control schemes of VSC have an important effect on the voltage stability. Several control methods of the VSC-HVDC networks to provide voltage enhancement during the AC voltage drops are presented in [5][6][7][8][9][10][11][12][13]. However, in those papers, the limits of the reference reactive current are always selected corresponding to different control modes, which will restrict the capability of VSC for reactive support, especially under serious voltage falls.…”
Section: Introductionmentioning
confidence: 99%